ANALISIS SENSITIVITAS 5 % KELAYAKAN USAHATANI PEMBIBITAN KARET “PAYUNG SATU” (Hevea brasilliensis) DI DESA BENTOK DARAT KECAMATAN BATI-BATI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
This research aim to Sensitivity Analyse 5 % Elegibility Farm Effort of Rubber Seed “Umbrella One” (Hevea Brasilliensis) in Bentok Darat with indicator of Net Present Value (NPV), Internal Rate of return (IRR) dan Net Benefit Cost Ratio (Net B/C) by using sensitivity analysis 5 % for the factor of production change. The results of the research showed Elegibility Farm Effort of Rubber Seed “Umbrella One” (Hevea Brasilliensis) in Bentok Darat is eligebility with Net Present Value (NPV) positif 226.328.495,34 NBCR 1,528 dan IRR 29,48 % by using 5 % sensitivity analyse.